Management of stage I testicular cancer. Issue 1 (11th January 2022) - Padayachee, Jerusha; Clark, Roderick; Warde, Padraig; Hamilton, Robert J.
Abstract : Purpose of review: Testicular cancer is the most common solid malignancy amongst young men, and a large proportion present with stage I disease. The options for management following radical orchiectomy are multifold. We review here approaches to treatment in this setting, providing an update on recent publications. Recent findings: At Princess Margaret Cancer Centre, we maintain a nonrisk adapted active surveillance approach. With a dedicated surveillance program using low-dose computed tomography imaging, patients are appropriately identified early for treatment on relapse. There are ongoing investigations into minimizing toxicities of treatments for relapse, and in particular, retroperitoneal lymph node dissection (RPLND) presents an attractive alternative. This, though, remains investigational in the setting of seminoma. Summary: Testicular cancer is a highly curable malignancy. In stage I disease, an active surveillance approach following radical orchiectomy is preferred, irrespective of risk-profile. This approach serves to limit the toxicity of adjuvant treatment in a significant proportion of patients, while maintaining excellent survival outcomes.